2.4 – Writing Linear Equations
2.4 – Writing Linear Equations Forms:
2.4 – Writing Linear Equations Forms: Standard Form
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form y – y 1 = m(x – x 1 )
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form y – y 1 = m(x – x 1 ) Example 1 - Write an Equation Given Slope & a Point
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form y – y 1 = m(x – x 1 ) Example 1 - Write an Equation Given Slope & a Point Write and equation in slope-intercept form for the line that has a slope of -3/2 and passes through (-4,1).
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form y – y 1 = m(x – x 1 ) Example 1 - Write an Equation Given Slope & a Point Write and equation in slope-intercept form for the line that has a slope of -3/2 and passes through (-4,1). Given:
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form y – y 1 = m(x – x 1 ) Example 1 - Write an Equation Given Slope & a Point Write and equation in slope-intercept form for the line that has a slope of -3/2 and passes through (-4,1). Given: m = -3/2
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form y – y 1 = m(x – x 1 ) Example 1 - Write an Equation Given Slope & a Point Write and equation in slope-intercept form for the line that has a slope of -3/2 and passes through (-4,1). Given: m = -3/2 (-4,1)
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form y – y 1 = m(x – x 1 ) Example 1 - Write an Equation Given Slope & a Point Write and equation in slope-intercept form for the line that has a slope of -3/2 and passes through (-4,1). Given: m = -3/2 (-4,1) Point-Slope
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form y – y 1 = m(x – x 1 ) Example 1 - Write an Equation Given Slope & a Point Write and equation in slope-intercept form for the line that has a slope of -3/2 and passes through (-4,1). Given: m = -3/2 (-4,1) Point-Slope y – y 1 = m(x – x 1 )
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form y – y 1 = m(x – x 1 ) Example 1 - Write an Equation Given Slope & a Point Write and equation in slope-intercept form for the line that has a slope of -3/2 and passes through (-4,1). Given: m = -3/2 (-4,1) Point-Slope y – y 1 = m(x – x 1 ) y – 1 = (-3/2)(x – (-4))
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form y – y 1 = m(x – x 1 ) Example 1 - Write an Equation Given Slope & a Point Write and equation in slope-intercept form for the line that has a slope of -3/2 and passes through (-4,1). Given: m = -3/2 (-4,1) Point-Slope y – y 1 = m(x – x 1 ) y – 1 = (-3/2)(x – (-4)) y – 1 = (-3/2)(x + 4)
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form y – y 1 = m(x – x 1 ) Example 1 - Write an Equation Given Slope & a Point Write and equation in slope-intercept form for the line that has a slope of -3/2 and passes through (-4,1). Given: m = -3/2 (-4,1) Point-Slope y – y 1 = m(x – x 1 ) y – 1 = (-3/2)(x – (-4)) y – 1 = (-3/2)(x + 4) y – 1 = (-3/2)x – 6
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form y – y 1 = m(x – x 1 ) Example 1 - Write an Equation Given Slope & a Point Write and equation in slope-intercept form for the line that has a slope of -3/2 and passes through (-4,1). Given: m = -3/2 (-4,1) Point-Slope y – y 1 = m(x – x 1 ) y – 1 = (-3/2)(x – (-4)) y – 1 = (-3/2)(x + 4) y – 1 = (-3/2)x – 6
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form y – y 1 = m(x – x 1 ) Example 1 - Write an Equation Given Slope & a Point Write and equation in slope-intercept form for the line that has a slope of -3/2 and passes through (-4,1). Given: m = -3/2 (-4,1) Point-Slope y – y 1 = m(x – x 1 ) y – 1 = (-3/2)(x – (-4)) y – 1 = (-3/2)(x + 4) y – 1 = (-3/2)x –
2.4 – Writing Linear Equations Forms: Standard Form Ax + By = C Slope-Intercept Form y = mx + b Point-Slope Form y – y 1 = m(x – x 1 ) Example 1 - Write an Equation Given Slope & a Point Write and equation in slope-intercept form for the line that has a slope of -3/2 and passes through (-4,1). Given: m = -3/2 (-4,1) Point-Slope y – y 1 = m(x – x 1 ) y – 1 = (-3/2)(x – (-4)) y – 1 = (-3/2)(x + 4) y – 1 = (-3/2)x – y = (-3/2)x – 5
Example 2 Write an Equation of a Perpendicular Line
Write an equation for the line that passes through (-4,3) and is perpendicular to the line whose equation is y = -4x – 1.
Example 2 Write an Equation of a Perpendicular Line Write an equation for the line that passes through (-4,3) and is perpendicular to the line whose equation is y = -4x – 1. (-4,3)
Example 2 Write an Equation of a Perpendicular Line Write an equation for the line that passes through (-4,3) and is perpendicular to the line whose equation is y = -4x – 1. (-4,3) m 1 = -4
Example 2 Write an Equation of a Perpendicular Line Write an equation for the line that passes through (-4,3) and is perpendicular to the line whose equation is y = -4x – 1. (-4,3) m 1 = -4 m 2 = ¼
Example 2 Write an Equation of a Perpendicular Line Write an equation for the line that passes through (-4,3) and is perpendicular to the line whose equation is y = -4x – 1. (-4,3) m 1 = -4 m 2 = ¼ So, write eq. through (-4,3) w/m 2 = ¼.
Example 2 Write an Equation of a Perpendicular Line Write an equation for the line that passes through (-4,3) and is perpendicular to the line whose equation is y = -4x – 1. (-4,3) m 1 = -4 m 2 = ¼ So, write eq. through (-4,3) w/m 2 = ¼. y – y 1 = m(x – x 1 )
Example 2 Write an Equation of a Perpendicular Line Write an equation for the line that passes through (-4,3) and is perpendicular to the line whose equation is y = -4x – 1. (-4,3) m 1 = -4 m 2 = ¼ So, write eq. through (-4,3) w/m 2 = ¼. y – y 1 = m(x – x 1 ) y – 3 = ¼(x – (-4))
Example 2 Write an Equation of a Perpendicular Line Write an equation for the line that passes through (-4,3) and is perpendicular to the line whose equation is y = -4x – 1. (-4,3) m 1 = -4 m 2 = ¼ So, write eq. through (-4,3) w/m 2 = ¼. y – y 1 = m(x – x 1 ) y – 3 = ¼(x – (-4)) y – 3 = ¼(x + 4)
Example 2 Write an Equation of a Perpendicular Line Write an equation for the line that passes through (-4,3) and is perpendicular to the line whose equation is y = -4x – 1. (-4,3) m 1 = -4 m 2 = ¼ So, write eq. through (-4,3) w/m 2 = ¼. y – y 1 = m(x – x 1 ) y – 3 = ¼(x – (-4)) y – 3 = ¼(x + 4) y – 3 = ¼(x) + ¼(4)
Example 2 Write an Equation of a Perpendicular Line Write an equation for the line that passes through (-4,3) and is perpendicular to the line whose equation is y = -4x – 1. (-4,3) m 1 = -4 m 2 = ¼ So, write eq. through (-4,3) w/m 2 = ¼. y – y 1 = m(x – x 1 ) y – 3 = ¼(x – (-4)) y – 3 = ¼(x + 4) y – 3 = ¼(x) + ¼(4) y – 3 = ¼(x) + 1
Example 2 Write an Equation of a Perpendicular Line Write an equation for the line that passes through (-4,3) and is perpendicular to the line whose equation is y = -4x – 1. (-4,3) m 1 = -4 m 2 = ¼ So, write eq. through (-4,3) w/m 2 = ¼. y – y 1 = m(x – x 1 ) y – 3 = ¼(x – (-4)) y – 3 = ¼(x + 4) y – 3 = ¼(x) + ¼(4) y – 3 = ¼(x)
Example 2 Write an Equation of a Perpendicular Line Write an equation for the line that passes through (-4,3) and is perpendicular to the line whose equation is y = -4x – 1. (-4,3) m 1 = -4 m 2 = ¼ So, write eq. through (-4,3) w/m 2 = ¼. y – y 1 = m(x – x 1 ) y – 3 = ¼(x – (-4)) y – 3 = ¼(x + 4) y – 3 = ¼(x) + ¼(4) y – 3 = ¼(x) y = ¼(x) + 4